TEKNOLOGI TERAPAN PEMANFAATAN LIMBAH CAIR PENCUCIAN KENDARAAN DENGAN METODE KOAGULASI DAN BIOFILTER MULTIMEDIA - Ain Khaer (Politeknik Kesehatan Makassar, 2016)
Waste water generated by the efforts of the washing of vehicles is directly discharged into water bodies or waterways will cause pollution in water bodies due to the characteristics of the washing process that generates the content of the detergent or ionic surfactants and COD concentration is high contained in the waste water washing the car and potentially causing a decrease in the quality of water bodies and cause unpleasant odors, it is caused by the nature of the detergent and oil are difficult to decompose, causing a decrease in self purification of the water body. Under these conditions, the necessary technology can be used to deal with waste car wash. This study aims to determine the ability of coagulation methods and biofilter in lowering levels of contaminants COD (chemichal Oxygen Demand) and the levels of detergentthe vehicle washing waste. This study is Praeksprimen with Pretest-Posttest Design draft that begins with a literature review, a preliminary study and research core that is making the tool coagulation and multimedia biofilter. Data on laboratory results were analyzed descriptively explained in the form of tables, graphs and narrative that describes the overall process that occurred during the study. Based on the research that the method of coagulation and multimedia biofilter reducing levels of COD (chemichal Oxygen Demand) washing the vehicle with the efficiency decreased by 55.99 mg / l (64.84%) and the content of detergent (MBAs) in wastewater effluents washing vehicles with efficiency penu (Runan of 86,05mg / l (40.05%) the processing is compliant with the standards in accordance Government Regulation No.82 of 2001 on processing of water Quality and water Pollution Control who will be discharged into water bodies class III, shall not exceed 200 mg / l.